2021
DOI: 10.3390/nu13041278
|View full text |Cite
|
Sign up to set email alerts
|

Breakfast and Exercise Improve Academic and Cognitive Performance in Adolescents

Abstract: This study examined the combined effects of breakfast and exercise on short-term academic and cognitive performance in adolescents. Eighty-two adolescents (64 female), aged 14–19 years, were randomized to four groups over a 4-hour morning: (i) a group who fasted and were sedentary (F-S); (ii) a group who ate breakfast but were sedentary (B-S); (iii) a group who fasted but completed a 30-minute exercise bout (F-E); and (iv) a group who ate breakfast and completed a 30-minute exercise bout (B-E). Individuals com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 42 publications
1
16
0
Order By: Relevance
“…In this prospective study, both men and women with a low frequency of breakfast intake tended to have an increased risk of poor AP, which is consistent with previous findings regarding elementary and high school students [17,18]. However, the findings regarding elementary and high school students may not be applicable to undergraduate students since the pre-universitylevel curriculum consists primarily of foundational and immovable courses, with the result that all students' waking times tend to be similar and students rarely wake up late enough to have to skip breakfast in the morning.…”
Section: Discussionsupporting
confidence: 92%
“…In this prospective study, both men and women with a low frequency of breakfast intake tended to have an increased risk of poor AP, which is consistent with previous findings regarding elementary and high school students [17,18]. However, the findings regarding elementary and high school students may not be applicable to undergraduate students since the pre-universitylevel curriculum consists primarily of foundational and immovable courses, with the result that all students' waking times tend to be similar and students rarely wake up late enough to have to skip breakfast in the morning.…”
Section: Discussionsupporting
confidence: 92%
“…Breakfast foods that do not produce high blood glucose levels after meals are preferred to improve students' cognitive performance. 40 Changes in the diet may negatively or positively affect health at all stages of life. Unfortunately, many developing countries focus only on nutritional deficiencies and do not focus on the concept of preventing chronic diseases by modifying food systems.…”
Section: Resultsmentioning
confidence: 99%
“…In line with this association, Adolphus et al ( 33 ) showed in a systematic review of studies with children and adolescents that, breakfast intake positively influences cognitive function compared to skipping breakfast. Likewise, Masoomi et al ( 34 ) and Kawabata et al ( 35 ) demonstrated that breakfast consumption had a positive influence on students' cognitive functions and school performance. Furthermore, Peña-Jorquera et al ( 36 ) indicated that adolescents who eat breakfast before cognitively demanding activities and who regularly include a high-quality breakfast have higher cognitive performance than their counterparts who do not.…”
Section: Discussionmentioning
confidence: 98%